An Efficient Hybrid Algorithm Combining Skeletonization MoM-PO and EDM for Solving Electromagnetic Radiation of Large-Scale Targets - Ma, Xianggang; Wang, Xing; Liu, Chunheng; Xu, Zhou; Wu, Jiahui; Liu, Ying (IEEE transactions on antennas and propagation, 2025)
The Method of Moments-Physical Optics (MoM-PO) algorithm, when applied to antenna arrays or antennas with complex surrounding structures, leads to a significant increase in the number of unknowns in the MoM region, resulting in higher memory consumption and reduced computational efficiency. To address this issue, a novel hybrid numerical method combining the skeletonization MoM-PO and Equivalent Dipole Moment (SKE-PO-EDM) is proposed for efficient electromagnetic radiation analysis of antennas mounted on electrically large structures. By utilizing the interpolation decomposition (ID) method, the skeleton basis functions for both the MoM and PO regions are derived separately, and the far-field interactions are compressed into the coupling between the skeleton basis functions. In addition to the self-impedance matrix and mutual-impedance matrix, the hybrid scheme introduces an innovative skeleton extraction technique suitable for the coupling matrix. After extracting the skeleton basis functions, the calculation of the impedance matrix elements is subsequently accelerated by EDM. Several numerical results show that the proposed approach significantly reduces both computation time and memory usage, while maintaining high accuracy.